2013
DOI: 10.3136/fstr.19.1149
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Collagen Peptide Ingestion on Blood Lipids in Rats Fed a High-Lipid and High-Sucrose Diet

Abstract: Increased protein intake frequently improves lipid profiles in humans and animals. To investigate the effects of collagen peptide ingestion on blood lipid profiles, 0.2 g/kg body weight collagen peptide was administered for 29 days to male Crlj:CD (SD) rats fed a high-lipid and high-sucrose diet, and their blood lipid levels were determined on days 1 and 28, and also on day 30 after overnight fasting. Food intake and body weight did not change with collagen peptide ingestion. Although triglycerides increased m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 18 publications
2
9
0
Order By: Relevance
“…1(A-C)). This is consistent with previous studies that examined the lipid-lowering effects of collagen ingestion in humans and animals (3,(11)(12)(13)(14)(15) . In the present study, significant differences were observed neither in the level of blood TAG nor in liver lipid contents, although our DNA microarray data suggest that liver lipid metabolism is enhanced by CP ingestion.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…1(A-C)). This is consistent with previous studies that examined the lipid-lowering effects of collagen ingestion in humans and animals (3,(11)(12)(13)(14)(15) . In the present study, significant differences were observed neither in the level of blood TAG nor in liver lipid contents, although our DNA microarray data suggest that liver lipid metabolism is enhanced by CP ingestion.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, significant differences were observed neither in the level of blood TAG nor in liver lipid contents, although our DNA microarray data suggest that liver lipid metabolism is enhanced by CP ingestion. Similar results that reduction in blood cholesterol without changes in TAG were also observed in our previous study in rats ( 14 ) . On the other hand, there are several reports that serum TAG is reduced by CP ingestion ( 11 , 13 ) , and one explanation for the reduction is described as increase in faecal excretion ( 13 ) .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The Col-Pep groups were administered food containing 0.15% or 0.3% Col-Pep (MW: 4,000–6,000; nitrogen content: 16.9%; fish-derived; Nippi Inc., Tokyo, Japan) such that a daily Col-Pep intake of 0.1 or 0.2 g/kg body weight was attained in the finisher period, respectively. The dose of 0.2 g/kg body weight was selected based on the effect reported in the porcine skin (62-day intake), the mouse skin (56-day intake), human skin (42-day intake), the rabbit Achilles tendon (56-day intake) and the rat blood lipids (29-day intake) [ 9 , 10 , 13 , 14 , 21 ]. To examine whether the effect of Col-Pep ingestion was collagen-specific or caused by ingestion of protein in general, the crude protein levels were adjusted to approximately equal amounts (days 0–21: 23.5%; days 22–49: 18.0%) using maize (Marui-Sangyo Co., Ltd., Nagano, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…However, this method has several side effects such as pain, erythema, and an infectious granulomatous reaction (15,16). Alternatively, several natural polymers including low-molecular-weight chitosan, gelatin, and chondroitin sulfate have been used as dietary supplements to accelerate fat reduction through several pathways (1719). Gelatin is an inexpensive alternative, readily available in nature, and widely used in diverse biomedical applications.…”
Section: Introductionmentioning
confidence: 99%